2014
DOI: 10.1680/gr.14.00016
|View full text |Cite
|
Sign up to set email alerts
|

Simplified finite-element modelling for tunnelling-induced settlements

Abstract: Tunnelling-induced ground surface settlement prediction still adopts empirical and analytical approaches; thus a step further in using a practical numerical analysis is now a challenging task. Because the deformation during tunnelling is a three-dimensional problem, several features were incorporated in two-dimensional analyses to capture aspects that are important in governing behaviour in the missing third dimension. This paper aims to present simplified methods for ground settlement computation of tunnellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…The results indicated that the hardening soil model (HSS) with small strain can provide better results compared to measured data. To date, more researchers (Likitlersuang et al , 2014; Liao et al , 2016) adopted the HSS with small strain to study the behavior of underground excavation. Therefore, the HSS with small strain is also adopted in this study to assess the behavior of the retaining walls, a set of analyses about the Kuhne Building (Case 10) are conducted by the commercially available PLAXIS 2D (Brinkgreve et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the hardening soil model (HSS) with small strain can provide better results compared to measured data. To date, more researchers (Likitlersuang et al , 2014; Liao et al , 2016) adopted the HSS with small strain to study the behavior of underground excavation. Therefore, the HSS with small strain is also adopted in this study to assess the behavior of the retaining walls, a set of analyses about the Kuhne Building (Case 10) are conducted by the commercially available PLAXIS 2D (Brinkgreve et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lade and Trads, 2014;Likitlersuang et al, 2014). This suggests that the tendency of lime-treated specimens containing salt to exhibit a dilative behaviour during drained loading results in an increase in the soil's shear strength within 7 d of curing.…”
Section: Drained Behaviourmentioning
confidence: 96%
“…In the last phase, the soil cluster inside the tunnel is deactivated, the same time the tunnel lining is activated. For further details about lining contraction and stress reduction method can be referred to Likitlersuang et al (2014). As mention, the procedure of lining contraction and stress reduction was done in the PLAXIS 2D software with the selected soil profile as shown in Figure 5.…”
Section: Finite Element Simulation Of Twin Tunnel Excavation Using LImentioning
confidence: 99%
“…Many geotechnical software developers apply FEM in their computational tool to solve geotechnical problems. However, the use of FEM in settlement prediction is still not that much accurate because of many factors such as simplified geometry and boundary condition, mesh generation, initial input of ground data and the type of constitutive model chosen for the analysis (Likitlersuang et al, 2014). To understand the behaviour of the soil, researchers developed soil constitutive model.…”
Section: Introductionmentioning
confidence: 99%